Impact of Supply Chain Strategy and Change Order on Contractors’ Cash Flow in Jordanian Construction Industry: A Case Study of Basic Educational School Construction - Qasem, Altayeb; Zaid, M. Murad; S.Gharaibeh, Emhaidy (International Journal of Supply Chain Management, 2019)
Jordan is employing major reforms in education sector. Not least of these innovations is the Building for basic education schools aims to improve the learning environment. Construction of such new schools are already going ahead in numerous areas of the Jordan. Although, the construction industry is a key player in the economy, creating both, employment and wealth, yet numerous projects experience extensive delays and thus surpass initial time and cost estimates. The most collective causes were appraised by using both, the data collected in a survey steered to residential projects consultant engineers, contractors, and owners, and interviews with senior professionals in the field, so supply chain strategy among them is the most important issue. Most correspondents established that, monetary difficulties faced by the contractor and too many change orders by the owner are the foremost causes of construction deferment. Stern weather states and changes in government regulations and laws categorized among the least important causes. To illustrate the implementation of the classification impact index model and to evaluate and quantify change orders impact on contractor’s cash flow, a case study is presented in this paper using data of real case study obtained from reputable construction company in Jordan involved in the construction of basic education school building. The project commenced from November 2012 till December 2013.